Uterus Didelphys with Pregnancy - Shahi, RR; Shrestha, MS; Thapa, GB; Basnet, SB; Khadka, G; Joshi, L (Medical Journal of Shree Birendra Hospital, 2012)
We report a case of 21 Yrs old female patient referred to the radiology department at Shree Birndra Hospital, to investigate primary infertility. She underwent hysterosalpingogram, both transabdominal & transvaginal ultrasound and MRI of the pelvis. The final diagnosis was Uterus Didelphys, which is a type of lateral fusion disorder of mullerian ducts. According to the American Fertility Society Classification of Mullerian Anomalies, Uterus Didelphys is a class III anomaly. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6449 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 40-43